2017
DOI: 10.1177/0021998317751283
|View full text |Cite
|
Sign up to set email alerts
|

TiO2 ceramic particles-reinforced aluminum matrix composite prepared by conventional, microwave, and spark plasma sintering

Abstract: Aluminum-10 wt% TiO2 metal matrix composites were fabricated with conventional, microwave, and spark plasma sintering processes. Aluminum and nano-sized TiO2 powders were mixed using a high-energy mixer, and the sintering process was done at 450℃ by spark plasma sintering and 600℃ under both microwave and conventional heating. The results showed microwave sintering led to form Al3Ti intermetallic compounds with flaky shape, while in the conventional heating at the same sintering temperature, Al3Ti was formed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(4 citation statements)
references
References 46 publications
1
3
0
Order By: Relevance
“…A comparison was made between the mechanical properties of the composites obtained and those found from the related literature for dense Al/Al 2 O 3 -TiO 2 materials obtained through different processes (Table 2). This finding is in good agreement with previously published results [3,8,12,21,[23][24][25]. Also, the reasons for lower values of hardness and tensile strength can be explained as follows:…”
Section: Structural Analysissupporting
confidence: 93%
See 1 more Smart Citation
“…A comparison was made between the mechanical properties of the composites obtained and those found from the related literature for dense Al/Al 2 O 3 -TiO 2 materials obtained through different processes (Table 2). This finding is in good agreement with previously published results [3,8,12,21,[23][24][25]. Also, the reasons for lower values of hardness and tensile strength can be explained as follows:…”
Section: Structural Analysissupporting
confidence: 93%
“…Ghasali et al [24] demonstrated that the formation of Al 3 Ti phases positively impacts the final mechanical properties of the aluminum matrix composite. Milman et al [26] pointed out that Al 3 Ti compounds act as an useful reinforcement for aluminum alloys due to significant properties such as low density, high hardness, good high-temperature properties.…”
Section: Structural Analysismentioning
confidence: 99%
“…Sintering process has marked influence on the mechanical properties of ceramic nanoparticle reinforced aluminium matrix nanocomposites. Ghasali et al [111] reported TiO 2 nanoparticle (particle size 100 nm) incorporated aluminium matrix nanocomposites produced by powder metallurgy route. Specimens were sintered by using three sintering modes namely conventional, microwave and spark plasma sintering process.…”
Section: Properties Of Ceramic Nanoparticle Reinforced Aluminum Matri...mentioning
confidence: 99%
“…[18][19][20][21] In the SPS process, high-speed heating under uniaxial pressure converts loose powder particles into high-density bulk parts with good mechanical properties. [22][23][24] It has been shown that sintering temperature is among the most important process parameters affecting the structural characteristics and mechanical properties of materials. S. Wei et al 25 found that the relative density of composites and the average grain size of TiB reinforcement increased simultaneously as the SPS sintering temperature in a TiB-reinforced titanium composite increased.…”
Section: Introductionmentioning
confidence: 99%